The Effect Of Mental Stress On The Results Of Iraqi Volleyball Clubs - Taleb Abd, Mohanad; Rumeeh, Ammar Fleah (International Journal of Psychosocial Rehabilitation, 2020)
The sample is (89) volleyball players from deferent seven clubs in Iraq, between the ages of 17 and 28 years (22.18 M,1.56 SD), who have experience in various domestic and international volleyball competitions, the questionnaire was distributed and their answers provided On the paragraphs of the questionnaire before the start of the Iraqi volleyball competition, the research problem lies in several questions, including whether volleyball players suffer from a state of exhaustion or physical exhaustion as a result of their exposure to mental stress? Does bad concentration and difficulty of controlling on emotional and physiological responses affect the result of the match? The research aims to identify the degree of mental stress among volleyball players, and the impact of the degree of mental stress in each match result, the limits of the search are determined in the players of Iraqi volleyball clubs participating in the gathering held in the city of Erbil on 24/1/2020, (89) players from the clubs (Al-Jaish, Al-Daghara, Peshmerga, Southern Gas, Police, Erbil, and Al-Bahri), and scale forms were distributed to the players in the hall of the Erbil Sports Club, the results showed a high impact of mental stress, and the sub-domains were psychological, physical, and cognitive , A significant positive impact on the results of some infidels Nautical and Southern Gas were assessed, but the effect was negative on the results of the remaining teams.